Complete genome sequence of Thermosediminibacter oceani type strain (JW/IW-1228PT). Issue 2 (September 2010) - Pitluck, Sam; Yasawong, Montri; Munk, Christine; Nolan, Matt; Lapidus, Alla; Lucas, Susan; Glavina Del Rio, Tijana; Tice, Hope; Cheng, Jan-Fang; Bruce, David; Detter, Chris; Tapia, Roxanne; et al.
Abstract Thermosediminibacter oceani (Leeet al. 2006) is the type species of the genusThermosediminibacter in the familyThermoanaerobacteraceae . The anaerobic, barophilic, chemoorganotrophic thermophile is characterized by straight to curved Gram-negative rods. The strain described in this study was isolated from a core sample of deep sea sediments of the Peruvian high productivity upwelling system. This is the first completed genome sequence of a member of the genusThermosediminibacter and the seventh genome sequence in the familyThermoanaerobacteraceae . The 2, 280, 035 bp long genome with its 2, 285 protein-coding and 63 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.